Diversity and composition of mosquito in stability of altered forest ecosystem (S.A.F.E) project area in Kalabakan, Sabah - Mahammad Imran Ebrahim (2020)
Changing of landscapes or environment can affect mosquito diversity, abundance and composition. The objectives of this study were to investigate the diversity, abundance and composition of mosquitoes as well as their interaction to changing environment condition especially their biting time behaviour within the Stability of Altered Forest Ecosystem (S.A.F.E.) Project field sites, Kalabakan, Sabah and Maliau Basin Conservation Area. Mosquito collection by using manual human landing catch technique was carried out in three study sites which were logged forest area (S.A.F.E. Project field site), oil palm plantation (S.A.F.E. Project field site), and primary forest area (Maliau Basin Conservation Area). A total of 1208 adults individuals and 268 larva were collected in six months of bi-monthly sampling collection (June 2016-April 2017). There were 25 adult mosquito species from nine genera of mosquitoes were caught in this study. Adult mosquitoes collection from primary forest in this study shows a high Shannon-weiner diversity value of H’=1.90 compared to logged forest sites, H’=1.45 and oil palm sites, H’=1.27. In term of mosquito abundance, logged forest area was considered abundant compared to oil palm and primary forest due to more abundance of possible vector mosquito such as Aedes, Culex and Anopheles mosquito in the area. One-way ANOVA analysis shows a significant variation in adult mosquitoes abundance between study sites (p<0.05). However, there is no significant difference in adult mosquitoes abundance for different sampling months. Based on the spearman correlation analysis, temperature and humidity shows a significant association with adult mosquito collections (p<0.05) for overall day time and night time collection. For mosquito biting time, based on the day-time sampling, logged forest area had peak biting around 3.00 pm similar with primary forest area but for oil palm the biting activity usually peaked when near 6.00 pm. For night-time sampling, logged forest area and oil palm plantation have similar peak biting around 7.00-8.00 pm while for primary forest area was around 6.00 pm. The implication of the changing of forested environment from previously undisturbed environment to disturbed environment may affect the diversity, composition, abundance and behaviour of mosquitoes especially for mosquito vector which responsible for disease transmissions.